Теоретичні основи професійної підготовки майбутніх фахівців лісового господарства: стратегічні цілі забезпечення екологічної стійкості - Біда Олена; Bida Olena; Орос Ільдіко; Orosz Ildikó; Oros Ildiko; Гончарук Віталій; Goncharuk Vitaliy (РВВ ЦДПУ ім. В. Винниченка, 2022)
Резюме. Однією з актуальних проблем сьогодення надалі залишається модернізація українських лісогосподарських шкіл як невід’ємної складової системи професійної освіти. Розглянуто особливості професійної підготовки фахівців лісогосподарського профілю за різними освітньо-кваліфікаційними рівнями в українських ЗВО. Проголошено засадничі принципи підготовки фахівців лісового господарства. Виокремлено заходи, що повинні бути перераховані в плані лісогосподарських заходів, доступному для громадськості й заходи, що є необхідними для покращення стану лісових ресурсів та ведення лісового господарства. Виокремимо стратегічні цілі забезпечення екологічної стійкості при управлінні лісами України.

Abstract. One of the most pressing problems today is the modernization of Ukrainian forestry schools as an integral part of the vocational education system. The article considered the peculiarities of professional training of forestry specialists at different educational and qualification levels in Ukrainian free economic zones. First of all, it is noted that the normative basis for the construction and organization of their educational work are state standards, which reflect a set of minimum requirements for the content and results of educational activities of higher education institutions at each level of higher education within each specialty. The basic principles of training of forestry specialists are its compliance with the existing and future needs of the forest industry; providing flexibility in the system of training specialists for their adaptation to the rapidly changing requirements of the national and international labor markets; integration of educational, research and innovation activities; logical relationship of master's degree programs with bachelor's degree programs. It is identified the measures that should be listed in the plan of forestry measures available to the public and the strategic goals of ensuring environmental sustainability in forest management of Ukraine. The need for integrity and non-dispersal of Ukraine's forest resources between different ministries and agencies is emphasized, which will enable effective management and use of forest resources on the basis of sustainable development, as is the case in European countries. Identified measures that are necessary to improve the condition of forest resources and forest management.
Theoretical fundamentals of professional training of future forestry professionals: strategic objectives of environmental protection
Keywords: професійна підготовка; майбутні фахівці лісового господарства; стратегічні цілі забезпечення екологічної стійкості; засадничі принципи підготовки фахівців лісового господарства; покращення стану лісових ресурсів та ведення лісового господарства; professional training; future forestry specialists; strategic goals of ensuring ecological sustainability; basic principles of training of forestry specialists; improvement of forest resources and forest management